1992
DOI: 10.2169/internalmedicine.31.1004
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein(a) Levels in the Nephrotic Syndrome.

Abstract: We investigated serum lipoprotein(a) [Lp(a)] levels in 20 patients with the nephrotic syndrome. Lp(a) levels in the nephrotic syndrome patients were significantly higher than those in a control group (30.4±22.5 vs 10.4± 17.7 mg/dl). Overall, the serum Lp(a) and lipid levels showed no relationship, but on an individual basis the serum Lp(a) level varied with the serum levels of total cholesterol and low density lipoprotein cholesterol in the nephrotic syndrome patients. Our findings suggest that a decrease in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Since Lp(a) is a potential independent risk factor for vascular disease in renal patients, addition al studies on the effects of co-3 FA in this patient category appear warranted. This is even more so since it has been suspected that proteinuria, possibly via a decrease in serum albumin, may lead to an increased hepatic Lp(a) synthesis [43], Therefore we elected to study the effects of co-3 FA in patients with chronic glomerular diseases, with the idea that a possible weak 'direct' effect on Lp(a) plas ma levels might be magnified by the reduction in protein uria occurring in these patients under co-3 FA treatment.…”
Section: Lipoprotein (A)mentioning
confidence: 99%
See 1 more Smart Citation
“…Since Lp(a) is a potential independent risk factor for vascular disease in renal patients, addition al studies on the effects of co-3 FA in this patient category appear warranted. This is even more so since it has been suspected that proteinuria, possibly via a decrease in serum albumin, may lead to an increased hepatic Lp(a) synthesis [43], Therefore we elected to study the effects of co-3 FA in patients with chronic glomerular diseases, with the idea that a possible weak 'direct' effect on Lp(a) plas ma levels might be magnified by the reduction in protein uria occurring in these patients under co-3 FA treatment.…”
Section: Lipoprotein (A)mentioning
confidence: 99%
“…Lp(a) levels have been reported to be elevated in kidney hemodialysis patients [23][24][25][26][27][28][29][30][31][32], where they appear to be an independent risk factor for cardiovascular disease [33], in untreated patients with end-stage renal failure [34][35][36][37][38][39], and in pro teinuric syndromes [40][41][42][43][44][45]. Renal transplantation in endstage renal disease partially corrects the abnormality [25,46], A correlation of Lp(a) levels with the degree of protein uria has indeed been suspected, with the hypothesis that the decrease in scrum albumin leads to an increased hepat ic Lp(a) synthesis [43], Omega-3 fatty acids (co-3 FA) have recently been pro posed as a useful adjunct therapy in patients with renal disease [47] where they may correct some of the lipid abnormalities (notably the hypertriglyceridemia [48]) and favorably alter renal vasodilatory reserve [49], We have recently reported that a 6-week course of dietary supple mentation with co-3 FA reduces proteinuria in patients with membranous glomerulonephritis and focal glomeru lar sclerosis [50]. In addition, some reports have indicated that plasma levels of Lp(a) were reduced by co-3 FA [51][52][53].…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al 22) reported the effects of hyperlipidemia on the pharmacokinetics of tadalafil in rats with experimental hyperlipidemia. They administered tadalafil to control rats and rats with poloxamer-407-induced hyperlipidemia.…”
Section: Discussionmentioning
confidence: 99%
“…They suggested that the alterations in the pharmacokinetics of tadalafil observed in hyperlipidemia rats may be attributable to a decrease in the unbound fraction of tadalafil in the plasma. 22) Kanno et al 23) suggested that a decrease in serum albumin led to increased hepatic lipoprotein synthesis. The observed range of the total cholesterol concentrations were 115-232 mg/dL in patient #1, and 92-144 mg/dL in patient #2, which were generally in the normal range.…”
Section: Discussionmentioning
confidence: 99%
“…Among these changes are an increase in serum total cholesterol, very-low and lowdensity-lipoprotein (VLDL and LDL) cholesterol, and triglycerides [1][2][3][4]. Recent studies have shown that serum lipoprotein (a) (Lp(a)) is also elevated in proteinuric patients [5][6][7][8]. Lp(a) is an LDL-like particle that contains apolipoprotein(a), which is covalently linked to apolipoprotein B-100 [9].…”
Section: Introductionmentioning
confidence: 99%